Rapid Progression of Primary Pulmonary NUT Midline Carcinoma: A Case Report and Literature Review - Gao, Rong; Yu, Jinyan; Lv, Xuejiao; Dong, Chunling (Respirology case reports, 2025)
ABSTRACT Primary pulmonary nuclear protein in testis (NUT) midline carcinoma (NMC) is a rare malignancy with characteristics that resemble those of squamous cell carcinoma, thus making it prone to both misdiagnosis and missed diagnosis. Primary pulmonary NMC is highly malignant and associated with poor prognosis, with no standardised effective treatments for patients who cannot undergo surgery. Concurrent or sequential chemoradiotherapy is considered an effective approach, and some targeted drugs have been clinically tested and demonstrated favourable results. We present a case of primary pulmonary NMC with cervical lymph node metastasis, in which the patient experienced temporary symptom relief after receiving anlotinib and chemotherapy combined with immunotherapy. However, the condition rapidly worsened, and the patient died within 1 month of diagnosis. We believe that combining anlotinib with chemotherapy as well as reducing the chemotherapy interval can be effective in the treatment of primary pulmonary NMC. We present the case of a patient with primary pulmonary nuclear protein in testis midline carcinoma, which is prone to misdiagnosis, who experienced poor treatment outcomes and a short overall survival duration. Anlotinib may provide an effective treatment option for select patient subgroups, and shortened chemotherapy could particularly benefit disease control in genetically defined cases.